Improvement of wastewater quality of Dhaleswari river, Bangladesh using submerged macrophyte Egeria densa - Parveen, Mahfuza; Abdullah, Muhammad; Rahman, S. M. Mahmudur; Chowdhury, Md. Azharul Haque; Khan, Md. Sadril Islam; Kamal, Pasha A.B.M. (Universitas Diponegoro, 2022)
Clean water is one of the significant goals among the 17 Sustainable Development Goals (SDGs), which will be achieved by at least 2030. It includes six outcome-oriented targets- improve water quality, wastewater treatment, ensure freshwater supplies are three of them. In Bangladesh, Freshwater ecosystem is continuously degraded due to rapid industrialization, which occurred along the riverside areas. In this context, laboratory-based work has been conducted to analyze the water quality of Dhaleshwari River, Bangladesh, which has already been polluted by industrial waste. The collected water samples were treated by submerged macrophyte Egeria densa to observe the changing water quality parameters. The growth of plants and roots were assessed after 10 days of exposure to three categories of water treatment. Initial and final water quality parameters were observed by the analysis of pH, EC, TDS, TSS, Acidity, Alkalinity, Total Hardness, Ca Hardness, COD, Sulphate (SO42-), Phosphate (PO43) Total Chlorine (Cl-) and Copper (Cu2+). The result showed that almost all the toxic parameters of water were reduced significantly at the end of the experiment. The present study hypothesized that submerged macrophyte E. densa can be used as a potential tool to upgrade the water quality of polluted rivers.Keyword: Clean water, Submerged macrophyte, SDG 6, Dhaleswari River, Freshwater ecosystem